Strategi Pemberdayaan UMKM Untuk Meningkatan Penjualan Kripik Tempe Hifary Desa Sampiran Kecamatan Talun Kabupaten Cirebon - Annisa Izzatul Jannah; Asri Isnaeni; Triyani (LPPM POLITEKNIK LP3I, 2023)
The community Service Program (KKN) is a community service program that is mandatory for university students in Indonesia. Thus, KKN not only provides benefits for students in terms of developing practical skills and understanding of society, but also supports the growth and aspirations of UMKM at the local level. In the KKN activity, group 1 conducted a survey of Small and Medium Enterprises (UMKM) Tempe Chips Hifary Jl. Kaligandu, RT 01/ RW 03, Sampiran, Talun, Cirebon Regency. The aim is to increase sales, develop the business to make it more advanced and collaborate between KKN and UMKM, which is a strategic step to move the wheels of the local economy while providing real social benefits. During the KKN activities, group 1 provided counseling and assistance to UMKM activist. Hopefully this activity can provide benefits for partners so they can develop their business.